Forty Days after the Great East Japan Earthquake: Field Research Investigating Community Engagement and Traumatic Stress Screening in a Post-Disaster Community Mental Health Training. (February 2013) - Tuerk, Peter W.; Hall, Brian; Nagae, Nobukazu; McCauley, Jenna L.; Yoder, Matthew; Rauch, Sheila A. M.; Acierno, Ron; Dussich, John
The current article describes the results of posttraumatic stress educational outreach and screening offered to 141 citizens of Japan who attended a public-service mental health training regarding post-disaster coping 40 days after a 6.8 Richter Scale earthquake, local and regional deaths, and an ongoing nuclear radiation threat. Attendees were given access to anonymous questionnaires that were integrated into the training as a tool to help enhance mental health literacy and bridge communication gaps. Questionnaires were turned in by a third of those in attendance. Among respondents, multiple exposures to potentially-traumatic events were common. More than a quarter of respondents met criteria for probable PTSD. Physical health and loss of sense of community were related to PTSD symptoms. Associations and diagnosis rates represented in these data are not generalizable to the population as a whole or intended for epidemiological purposes; rather, they are evidence of a potentially useful approach to post-disaster clinical screening, education, and engagement. Results are presented in the context of previous findings in Japan and ecologically-supportive post-disaster field research is discussed.